Oral History Program Interview: Clarence William Graham - Graham, Clarence William
Born in McClain County, Indian Territory, Oklahoma in 1900, Graham came to California in 1924. He came with his family to California in 1924. This interview describes making moonshine, how The Grapes of Wrath was impressionable on locals as the truth about the camps, unsanitary ditch and government camps, fruit tramps, grower camps having nicer housing, and the Japanese as growers and how they were interned.